Dampak Pelanggaran Etika Profesi Guru Terhadap Keprofesionalannya Dalam Proses Pembelajaran - Devi Putri Thesia; Eshaulin Br Sembiring; Yosua Gabe Maruli Sijabat; Sri Yunita (Lembaga Pengembangan Kinerja Dosen, 2024)
The code of ethics is a standard of teacher behavior that aims in general to position teachers as teachers and a profession that is honorable, noble, and dignified. At this time, what often happens in the world of education, especially in schools, there are still educators or teachers who violate the code of ethics who do not show their professionalism in teaching. The method that the author uses in this research is a qualitative method using literature study, namely conducting research by collecting information from books and journals. Violations of the code of ethics committed by teachers can have an impact on the lack of quality in learning and not achieving learning objectives. Keywords :, ,